Editorial for Special Issue “Recent Advances in Fractional Differential Equations, Delay Differential Equations and Their Applications” - Omar Bazighifan (Fractal and Fractional, 2022)
Differential equations, both fractional and ordinary, give key tools in understanding the mechanisms of physical systems and solving various problems of nonlinear phenomena [...]